SWOT-AHP hybrid method for ranking the strategies in the shipbuilding sector - Popescu, Gabriel; Gasparotti, Carmen (Journal of Business Economics and Management, 2022)
The paper outlines the most important shipbuilding strategies in Romania that would allow this industry to increase its performance to be competitive. The research is mainly based on the collection of information from experts in the field from ANCONAV (Romanian Shipbuilders Association), specialists in design and production, and shipyard managers in Romania. The SWOT analysis was based on this information and was the starting point in formulating the strategies. The quantitative determination of the importance of each factor and sub-factor from the SWOT matrix in view of ranking the strategies, but also the verification of the points of view of the experts in the field were performed using the Analytical Hierarchy Process Method (AHP), using Excel applications. The obtained results consisted in identifying the internal and external environmental factors and formulating the main strategies with positive effects on the Romanian naval sector (the development of a Romanian cluster, the consolidation of the position on the global ship market through aggressive marketing, investments regarding the construction of ecological ships, the development of centers of excellence for exploiting the research-development-innovation capacity, the limitation of highly-skilled labor migration, expanding the digitalization, and developing a marketing policy to promote the national shipbuilding companies globally).